2015
DOI: 10.1161/circinterventions.115.002653
|View full text |Cite
|
Sign up to set email alerts
|

Procedural Results and Clinical Outcomes of Transcatheter Aortic Valve Implantation in Switzerland

Abstract: Key Words: aortic valve stenosis ◼ bleeding ◼ transcatheter aortic valve replacement ◼ transcatheter heart valve ◼ transcutaneous aortic valve implantation ◼ vascular complications

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
20
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(25 citation statements)
references
References 39 publications
3
20
0
2
Order By: Relevance
“…[1][2][3][4][5][6][7] Consequently, most patients undergoing TAVI are old and have multiple comorbidities. [1][2][3][4][5][6][7][8][9] In these patients, functional aspects, especially cognitive function, are highly relevant.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6][7] Consequently, most patients undergoing TAVI are old and have multiple comorbidities. [1][2][3][4][5][6][7][8][9] In these patients, functional aspects, especially cognitive function, are highly relevant.…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6][7] Consequently, most patients undergoing TAVI are old and have multiple comorbidities. [1][2][3][4][5][6][7][8][9] In these patients, functional aspects, especially cognitive function, are highly relevant. [8][9][10][11] In a previous analysis, we showed that patients with impaired cognitive function before TAVI have an ≈3-fold increased risk of mortality at 1-year follow-up as compared with those with normal cognitive function and that cognitive impairment is also associated with increased morbidity as well as with disability and reduced quality of life after TAVI.…”
mentioning
confidence: 99%
“…In addition, as novel generation valves appear to have addressed the issue of PVL, other interactions – conduction abnormalities in particular – need to be predicted by the simulation program. For instance, the incidence of moderate or severe aortic regurgitation after Lotus and Edwards Sapien 3 valve implantation is 1% but are associated with a new pacemaker implantation rate of 32 and 17%, respectively [13, 14]. …”
Section: Discussionmentioning
confidence: 99%
“…Both conditions are of clinical importance since, depending on the patient’s baseline risk, they may be associated with impaired prognosis [1012]. Novel generation devices have to a large extent addressed the issue of PVL but are associated with a higher incidence of conduction abnormalities in comparison to preceding valve designs [13, 14]. Yet, PVL still occurs and a number of other (rare) complications can happen such as aortic root rupture, coronary obstruction or valve embolisation [1518].…”
Section: Introductionmentioning
confidence: 99%
“…These results have been observed in other contemporary studies. 19,20 However, the association between the grade of PVR and the degree of AVC across the several iterations of the same valve prosthesis has not been investigated so far. In the present study, we demonstrated that the grade of significant PVR is independently associated with the degree of AVC according to Agatston calcium scoring (log-transformed Agatston score, odds ratio 3.478, 95% CI 1.424 to 8.498, p ¼ 0.006).…”
Section: Discussionmentioning
confidence: 99%